Vision zero: from accident prevention to the promotion of health, safety and well-being at work - Zwetsloot, Gerard; Leka, Stavroula; Kines, Pete (Taylor & Francis, 2017)
There is growing attention in industry for the Vision Zero strategy, which in terms of work-related health and safety is often labelled as Zero Accident Vision or Zero Harm. The consequences of a genuine commitment to Vision Zero for addressing health, safety and well-being and their synergies are discussed. The Vision Zero for work-related health, safety and well-being is based on the assumption that all accidents, harm and work-related diseases are preventable. Vision Zero for health, safety and well-being is then the ambition and commitment to create and ensure safe and healthy work and to prevent all accidents, harm and work-related diseases in order to achieve excellence in health, safety and well-being. Implementation of Vision Zero is a process – rather than a target, and healthy organizations make use of a wide range of options to facilitate this process. There is sufficient evidence that fatigue, stress and work organization factors are important determinants of safety behaviour and safety performance. Even with a focus on preventing accidents these additional factors should also be addressed. A relevant challenge is the integration of the Vision Zero into broader business policy and practice. There is a continued need more empirical research in this area.